Morphology of the incisura fibularis in the Turkish population - Misir, Abdulhamit; Uzun, Erdal; Tursem Tokmak, Turgut (Annals of Medical Research, 2021)
Aim: Morphology of the distal tibiofibular syndesmosis plays an important role in the pattern of ankle fracture and reduction strategy. This study aimed to describe the normal morphology of the distal tibiofibular syndesmosis in a Turkish population. Materials and Methods: All analyzes were based on 349 computed tomography images, contributed by 265 male and 84 female patients. The following features were measured on axial images: the depth of the incisura fibularis, anterior tibiofibular depth, posterior tibiofibular depth, anterior-posterior length of the fibula, mediolateral width of the fibula, version of the incisura fibularis, anterior tubercle length, posterior tubercle length, and tibiofibular engagement. All measure ts were performed by an orthopedic surgeon and an experienced musculoskeletal radiologist, repeated at a 2-week interval. Results: The most common morphology of the incisura fibularis was concave (C-shape, depth >4 mm, 66.5%), followed by a shallow morphology (I-shape, depth 4 mm, 18.3%), and r-shape (15.2%). Significant between-sex differences were identified for depth of the incisura fibularis, posterior tibiofibular depth, anterior-posterior length of fibula, mediolateral width of the fibula, anterior tubercle length, posterior tubercle length, tibiofibular engagement, and incisura fibularis height. Across the three morphologies (C-, I- and r-shape), there was a significant difference in the anterior tibiofibular depth, anterior-posterior length of the fibula, degree of retroversion of the incisura fibularis, and extent of tibiofibular engagement (p0.001). Conclusions: Knowledge of the variability in the morphology and measurements of the features of the incisura fibularis can be useful in the diagnosis of syndesmosis injury and lowering the risk of malreduction during surgery of ankle fractures among Turkish individuals.